The Relationship between Maternal Characteristics and Health Workers Role on Early Complementary Feeding in the Era of the COVID-19 Pandemic - Ramadhani, Fitri; Frety, Endyka Erye; Husada, Dominicus (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Early complementary feeding in Indonesia, especially in Palu city, is still relatively high and should focus. Early complementary feeding can negatively affect babies, such as being more susceptible to disease than babies who only get breast milk. This study aims to analyze the relationship between maternal characteristics and the role of health workers on early complementary feeding in the Pantoloan Public Health Center, Palu City. Subjects and Method: This research is quantitative research with a cross-sectional study. The study was conducted in all Integrated Healthcare Centers in the Pantoloan Health Center working area from April to October 2021. The research sample was mothers aged 0-6 months with inclusion and exclusion criteria. Sampling is done by total sampling. Complementary feeding was the dependent variable in this study. The independent variables in this study were the mother's characteristics in the form of age, education, occupation, maternal parity, and the role of health workers. This Data was collected using a questionnaire and analyzed by univariate and bivariate tests. Results: The results showed that there was a significant relationship between maternal characteristics in the form of age (p= 0.031), education (p= 0.002), occupation (p= 0.035), parity (p= 0.027), and the role of health workers (p= 0.046) in the provision of early complementary feeding in the work area of the Pantoloan Public Health Center, Palu City. Conclusion: Early complementary feeding can be influenced by maternal characteristics such as age, education, occupation, and parity, as well as the influence of the role of health workers.